SISTEM INFORMASI BERBASIS WEB PRODUK UNGGULAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KOTA SEMARANG - Kristiyanti, Mariana; Rahmasari, Lisda (Proceeding SENDI_U, 2015)
On his way, found that the development of Micro, Small and Medium Enterprises in Semarang city impressed slow.This is due to failed in adopting information technology in its efforts to. When compared with large companies, theyalways have concern for the use of new technologies in support of its business. The system used by Micro, Small andMedium Enterprises (UMKM) in Semarang still utilize the traditional system, While this has become moresophisticated and the existence of modern technology. It is the lack of opportunities to be able to compete in theglobal effort if this system to be. Because of that, to increase the capacity of Micro, Small and Medium Enterprises(UMKM) in technology Semarang, Web based which is expected to be able to resolve some of the problems faced byMicro, Small and Medium Enterprises (UMKM) in Semarang in the introduction of the superior productsKey words : Information Sistem, Website, Superior Products, UMKM